The Effect of Rural Bridge Infrastructure on Agricultural Economic Growth In Indonesia : Bridge Infrastructure and Agricultural Economic (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2024)
Background and purpose - Bridge infrastructure is considered a core infrastructure that can increase economic growth in the agricultural sector because it can facilitate the distribution of agricultural products. This study aims to analyze the effect of bridge infrastructure on economic growth in the agricultural sector in Indonesia. Methodology - This study uses secondary data obtained through the official website of the Central Statistics Agency (BPS) and the Ministry of Public Works and Public Housing (PUPR) from 2012 to 2021 in a total of 29 provinces in Indonesia. Data analysis uses panel data regression analysis method using Eviews12 software. Findings - The results showed that the percentage of bridge infrastructure in good condition has a positive significant effect (0.0232 < 0.05); the percentage of bridge infrastructure in bad condition has a negative significant effect (0.0050 < 0.05); the total population has a positive significant effect (0.0000 < 0.05); while the land area has no significant effect (0.5067 > 0.05). Implications - Attention and maintenance of bridge infrastructure by the Ministry of Public Works and Housing, along with precise policy implementation by local government officials, are crucial for supporting the economic growth of Indonesia's agricultural sector